Atomic-scale phonon scatterers in thermoelectric colusites with a tetrahedral framework structure. Issue 1 (5th December 2018) - Suekuni, Koichiro; Shimizu, Yuta; Nishibori, Eiji; Kasai, Hidetaka; Saito, Hikaru; Yoshimoto, Daichi; Hashikuni, Katsuaki; Bouyrie, Yohan; Chetty, Raju; Ohta, Michihiro; Guilmeau, Emmanuel; Takabatake, Toshiro; et al.
Abstract : Atomic-scale defects/disorded states induced by sulfur sublimation are responsible for reduced lattice thermal conductivity of thermoelectric colusite. Abstract : Copper-based chalcogenides with tetrahedral framework structures have been attracting increasing attention as environmentally friendly thermoelectric materials. A representative group of such thermoelectric chalcogenides is the Cu26 A2 M6 S32 (A = V, Nb, Ta; M = Ge, Sn) family of colusites, which exhibit low electrical resistivity, a large Seebeck coefficient, and low thermal conductivity; these properties are necessary for efficient thermal-to-electronic energy conversion. Here, we show the impact of crystal structure on the lattice thermal conductivity of colusite with A = Nb, M = Sn. The crystal structure can be modified by controlling the cationic compositions and the deficiency in the sulfur content as Cu26− x Nb2 Sn6+ x S32− δ . The Cu/Sn ratio is found to be the key parameter for exsolution into distinct phases with ordered and disordered arrangements of cations. For the ordered-structure phase, sulfur sublimation induces atomic-scale defects/disordered states including interstitial defects, anti-site defects, and site splitting, which function as strong phonon scatterers, and the lowest lattice thermal conductivity of ∼0.5 W K −1 m −1 is achieved for the modified ordered structure. This finding provides a simple approach to modifying the crystal structure of thermoelectric chalcogenides via the loss of anions to reduce their lattice thermal conductivity.